Uromycladium tepperianum, the gall rust fungus from Falcataria moluccana in Malaysia and Indonesia. - Sardula, Sri Rahayu; Lee, Su See; Ab Shukor, Nor Aini (Springer Link, 2010)
Batai (Falcataria moluccana) is a valuable tree species for forest plantations in Malaysia and Indonesia. Since 1993, a gall rust disease has caused severe damage to all growth stages, from seedlings in the nursery to mature trees in the field. To identify the fungus causing gall rust disease on F. moluccana in Malaysia and Indonesia, study of the mode of infection and changes in the anatomy of infected cells were carried out in the anatomy laboratory. The disease in Malaysia and Indonesia is caused by Uromycladium tepperianum. The fungus produces three longitudinally ridged teliospores on each head, with spores measuring 13–20 μm wide and 17–28 μm long. The fungus is microcyclic, completing its entire life cycle on F. moluccana. This study confirmed that the teliospores themselves cannot infect the host. Under favorable conditions, about 10 h after inoculation, teliospores germinate to produce basidiospores that form penetration pegs about 6 h later, and it is this peg which penetrates the host cells directly through the epidermis. Pycnia, recognized as small brown pustules, break through the epidermis about 7 days after inoculation.